Peptide Selection of MMP-1 for Electrochemical Sensing with Epitope-Imprinted Poly(TPARA-co-EDOT)s - Mei-Hwa Lee; Cheng-Chih Lin; Piyush Sindhu Sharma; James L. Thomas; Chu-Yun Lin; Zofia Iskierko; Paweł Borowicz; Chien-Yu Lin; Wlodzimierz Kutner; Chien-Hsin Yang; Hung-Yin Lin (Biosensors, 2022)
Instead of molecularly imprinting a whole protein molecule, imprinting protein epitopes is gaining popularity due to cost and solubility issues. Belonging to the matrix metalloproteinase protein family, MMP-1 is an interstitial collagenase that degrades collagen and may be involved in cell migration, cell proliferation, the pro-inflammatory effect, and cancer progression. Hence, it can serve as a disease protein biomarker and thus be useful in early diagnosis. Herein, epitopes of MMP-1 were identified by screening its crystal structure. To identify possible epitopes for imprinting, MMP-1 was cleaved in silico with trypsin, pepsin at pH = 1.3, and pepsin at pH > 2.0 using Peptide Cutter, generating peptide fragments containing 8 to 12 amino acids. Five criteria were applied to select the peptides most suitable as potential epitopes for MMP-1. The triphenylamine rhodanine-3-acetic acid (TPARA) functional monomer was synthesized to form a stable pre-polymerization complex with a selected template epitope. The complexed functional monomer was then copolymerized with 3,4-ethoxylenedioxythiophene (EDOT) using potentiodynamic electropolymerization onto indium–tin–oxide (ITO) electrodes. The composition of the molecularly imprinted poly(TPARA-co-EDOT) (MIP) was optimized by maximizing the film’s electrical conductivity. Cyclic voltammetry was used to determine MMP-1 concentration in the presence of the Fe(CN)63−/Fe(CN)64− redox probe actuating the “gate effect.” A calibration curve was constructed and used to determine the usable concentration range and the limit of detection as ca. 0.001 to 10.0 pg/mL and 0.2 fg/mL MMP-1, respectively. Finally, the MMP-1 concentration in the A549 human lung (carcinoma) culture medium was measured, and this determination accuracy was confirmed using an ELISA assay.